(untitled) (Indonesian Journal Of Social Issues and Multidisiplinary Studies, 2026)
This research is grounded in the importance of students’ ability to read, understand, and memorize the Al-Qur’an as a fundamental competency in Islamic educational institutions. Memorization of Juz 30 is a primary target in tahfiz learning because it consists of short surahs that are closely connected to students’ daily worship practices. Therefore, effective learning strategies are required to support students in achieving optimal memorization outcomes. This study employs a qualitative approach with a descriptive research design. Data were collected through observations of tahfiz learning activities, interviews with educators and students, and documentation related to the planning, implementation, The implementation of appropriate, well-planned and evaluation of Qur’anic memorization learning. The collected data were analyzed systematically to describe the strategies implemented by educators in the tahfiz learning process. The findings indicate that educators apply various strategies to enhance students’ memorization abilities. These strategies include the talaqqi and tasmi’ methods to ensure accuracy in recitation, structured repetition (tikrār) to strengthen memory retention, and the use of audio media as supporting tools for memorization. In addition, educators form memorization groups to encourage cooperation among students and provide motivation and rewards as psychological reinforcement. The application of these strategies has proven effective, as reflected in improvements in students’ makhraj and tajwid accuracy, recitation fluency, and consistency in achieving memorization targets. The study concludes that educators play a crucial role in the success of tahfiz learning. The implementation of appropriate, well-planned, and continuous strategies can optimize the mastery of Juz 30 memorization among Madrasah Ibtidaiyah students.